TREATMENT RESULTS OF CHROMIC OSTEOMYELIT OF THE LONG BONER - Karakurt, Lokman; Yılmaz, Erhan; Ayhan, Ömer; Serin, Erhan (Fırat University, 2001)
Aim:This study consists of our treatment approach in chronic osteomyelitis, treatment difficulties, clinical and radiological results. Material and Methods: Thirty-three cases were managed between November 1991 and January 1999. Chronic osteomyelitis were found as 87 percent (20 cases) of the 23 patients with long bone osteomyelitis. In this study, 15 cases of chronic osteomyelitis were evaluated. Ten cases were men and 5 cases were women. There were 8 tibial, 4 femoral, 2 fibular and 1 ulnar osteomyelitis. The mean age was 15 years (3-47 years) and the mean follow-up period was 42.5 months, (7-120 months). We used only antibioterapy in 2 cases and antibioterapy + surgery in 13 cases. Eight Fenestration (F) + Secestrectomy (S) + Curetaj (C) + Washing (W), two F+S + C + W + Myoplasty, one F+S+C+W + Antibiotic chain, one parsiel fibular resection and one drenaj were created. Results: When the results were evaluated according to the clinical and radiological criterion of Lauschke et al and 7 (47 percent) good, 2 (13 percent) satisfactory, 6 (40 percent) bad results were found. Conclusion: Because of the late hospitalization, sending difficulties, lack of insurance and monetary difficulties, our percentage of chronic osteomyelitis was high in comparison to the literature. So that, chronic osteomyelitis was still being important problem in our region.

Amaç: Bu çalışma; kronik osteomyelit olgularındaki tedavi yaklaşımlarımızı, karşılaştığımız zorlukları, klinik ve radyolojik sonuçlarımızı içermektedir. Gereç ve Yöntem: Kasım 1991-Ocak 1999 tarihleri arasında 33 olgu tedavi edildi. İzlemi yapılabilen 23 uzun kemik osteomyelit hastasındaki kronik osteomyelit oranı %87 (20 hasta) idi. Ortalama yaş 15 (3-47) ve ortalama izlem süresi 42.5 ay (7-120) olan 15 kronik osteomyelit olgusu çalışmaya dahil edildi. Onbeş olgunun 8'i tibia, 4'ü femur, 2'si fibula ve 1'i ulna yerleşimliydi. Hastaların 10'u erkek, 5'i bayandı. İki olguya sadece antibiyoterapi ve 13 olguya ise antibioterapi + cerrahi uygulandı. Cerrahi uygulanan 13 olgunun 8'ine Fenestrasyon (F) + Sekestrektomi (S) + Küretaj (K) + Yıkama (Y), 2'sine F+S+K+Y+ Myoplasty, 1'ine F+S+K+Y+ Antibiyotik zinciri, Tine fibula parsiyel eksizyonu ve 1'ine de sadece apse drenajı yapıldı. Bulgular: Lauschke ve ark.'nın klinik ve radyolojik kriterlerine göre değerlendirildiğinde; 7 (%47) olguda iyi, 2 (%13) olguda orta, 6 (%40) olguda ise kötü sonuç elde edildi. Sonuç: Kronik osteomyelit oranımız literatüre göre yüksek bulundu. Hekime başvuruda gecikme, sevk zorlukları, sosyal güvence eksikliği ve maddi sorunların bunda etkili olduğu kanısına vardık. Sonuç olarak, kronik osteomyelit halen bölgemizde önemli bir sorun olmaya devam etmektedir.
UZUN KEMİK KRONİK OSTEOMYELİT OLGULARINDAKİ TEDAVİ SONUÇLARIMIZ